Correction: Corrigendum: Ubiquitin ligase RNF20/40 facilitates spindle assembly and promotes breast carcinogenesis through stabilizing motor protein Eg5 - Yang Duan (Nature Portfolio, 2016)
Nature Communications 7: Article number: 12648 (2014); Published: 25 August 2016; Updated: 4 November 2016 In Fig. 1a of this Article, the locations of labels for TPM3 and RPS3 protein bands are incorrect. The correct version of Fig. 1 appears below.